Rubisco kinetic acclimation at the holoenzyme level - Bryce Askey; Maddie Ceminsky; Elena Scott; Yongsheng Wang; Zhen Guo Oh; Stavros Azinas; Arthur Laganowsky; Laura Helen Gunn (Proceedings of the National Academy of Sciences, 2026)
In plants, the CO 2 -fixing enzyme Rubisco is hexadecameric, with each mature holoenzyme containing eight small subunits (SSus). Many plants express multiple SSus and vary their expression in response to environmental cues. Previous work indicates that this may allow fine-tuning of Rubisco’s performance in a variable environment (i.e., kinetic acclimation). Despite SSu pools being heterogeneous and dynamic, nearly no evidence exists for holoenzyme-level heterogeneity. Here, we characterized the structural and kinetic plasticity of Rubisco. We first established that SSu-heterogeneous Rubisco exists in Arabidopsis thaliana and quantified the prevalence of heterogeneity. We found SSu-heterogeneous Rubisco to make up over half of the Rubisco pool when heterologously expressed. This Rubisco contained at least four unique SSu ratios, indicating a variety of holoenzyme arrangements are possible. We then tested the kinetic effect of different SSus and found heterogeneity to have an antagonistic effect on substrate and inhibitor affinity. Kinetic differences between the SSus correlated with changes in local flexibility, and cryo-EM analysis illustrated a structural mechanism through which SSus may influence catalysis. Our kinetic and structural findings align with the hypothesized role of SSus in kinetic acclimation, as we observed the warm temperature-expressed SSu of A. thaliana to confer a stabilizing effect to the active site relative to the cool temperature-expressed SSu. This increase in stability manifested as a reduction in flexibility and increase in substrate affinity, indicating that fine-tuning of local stability may underlie Rubisco kinetic acclimation.